RELATIONSHIP BETWEEN MOTOR COMPETENCE (REAL AND PERCEIVED), PHYSICAL ACTIVITY PLAY AND SEDENTARY BEHAVIOR IN PRESCHOOLERS: A LITERATURE REVIEW - Cunha, Liliana (2022)
Abstract The purpose of this chapter is to conduct a literature review on the relationship between motor competence (real and perceived), physical activity play and sedentary behavior in preschool children with typical development. In general, the reviewed studies indicate that object control skills are positively correlated with physical activity play and negatively correlated with sedentary behavior. There are inconsistencies in scientific evidence regarding the correlation between locomotor skills and physical activity play, and some studies found a negative correlation between locomotor skills and sedentary behavior. Regarding perceived motor competence, most of the studies did not find a significative association with physical activity play, as well as with sedentary behavior. In conclusion, most studies found significant associations between (real) object control skills and physical activity play, while the relationship between (real) locomotor skills and physical activity play was less evident. Finally, the relationship of perceived motor competence with physical activity play and sedentary behavior was less conclusive. Resumo O objetivo deste capítulo é realizar uma revisão da literatura sobre a relação entre a competência motora (real e percebida), o jogo de atividade física e o comportamento sedentário em crianças de idade pré-escolar com desenvolvimento típico. De um modo geral, os estudos revistos indicam que as habilidades de controlo de objetos estão significativamente correlacionadas com o jogo de atividade física, e negativamente correlacionadas com o comportamento sedentário. Existem inconsistências na evidência científica relativamente à correlação entre as habilidades locomotoras e o jogo de atividade física, e alguns estudos indicaram uma correlação negativa entre as habilidades locomotoras e o comportamento sedentário. No que diz respeito à perceção de competência motora, a maioria dos estudos não encontrou associação com o jogo de atividade física, assim como com o comportamento sedentário. Em conclusão, a maioria dos estudos encontrou associações significativas entre as habilidades de controlo de objetos (real) e o jogo de atividade física, enquanto a relação entre as habilidades locomotoras (real) e o jogo de atividade física foi menos evidente. Por fim, a associação entre a perceção de competência motora e o jogo de atividade física e comportameno sedentário não foi conclusiva.